A audiência pública como instrumento processual de efetivação do princípio do contraditório: uma análise das audiências públicas realizadas pelo Supremo Tribunal Federal - Espindula, Vanessa Machado (2011)
The research analises the public audiences already realized by the Supreme Federal Court (STF) with the purpose to answer the following question: The public audience, as realized by the Supreme Federal Court, is a processual instrument to accomplish the principle of the contradictory? To answer this question, the first chapter analised the principle of the contradictory in the Democratic State of Law. It analised how the principle of the contradictory influences the jurisdictional activity and how it must be developed by the STF in agreement to the current conception of this principle. In the second chapter, the origin of the use of the public audiences by the Judicial Power was identified, as well as the existence of a prevision in the legal system to the realization of a public audience. It was verified that there are limits to the realization of this processual act by the Judicial Power. In the third chapter, the hypotheses that the STF realized public audiences were identified. The procedure adopted by the STF was analised, as weel as the existence of similarities and differences between the public audiences already realized by the STF. At last, it was made an analysis of the arguments that were presented in the public audiences and of the decisions pronouced by the STF. At the end, it concluded that the public audiences realized by the Supreme Federal Court were processual instruments to accomplish the principle of the contradictory.